2003
DOI: 10.1007/s10071-003-0172-0
|View full text |Cite
|
Sign up to set email alerts
|

The use of prosodic cues in language discrimination tasks by rats

Abstract: Recent research with cotton-top tamarin monkeys has revealed language discrimination abilities similar to those found in human infants, demonstrating that these perceptual abilities are not unique to humans but are also present in non-human primates. Specifically, tamarins could discriminate forward but not backward sentences of Dutch from Japanese, using both natural and synthesized utterances. The present study was designed as a conceptual replication of the work on tamarins. Results show that rats trained i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 13 publications
3
54
0
Order By: Relevance
“…First, young infants seem to discriminate language differences or prosodic structures of languages by using general auditory mechanisms shared by other animals. Tamarin monkeys and rodents discriminate language differences and forward vs. backward speech as young infants do (Ramus et al, 2000;Toro et al, 2003). Second, in both NIRS and fMRI studies, activations observed during reversed speech were weak but they were also left-dominant.…”
Section: Developmental Neurobiologymentioning
confidence: 90%
“…First, young infants seem to discriminate language differences or prosodic structures of languages by using general auditory mechanisms shared by other animals. Tamarin monkeys and rodents discriminate language differences and forward vs. backward speech as young infants do (Ramus et al, 2000;Toro et al, 2003). Second, in both NIRS and fMRI studies, activations observed during reversed speech were weak but they were also left-dominant.…”
Section: Developmental Neurobiologymentioning
confidence: 90%
“…However, the effect disappeared when stimuli were played backward. These results have also been replicated with rats, using operant training methods as opposed to spontaneous techniques (Toro, Trobalon, & Sebastian-Galles, 2003, 2005.…”
Section: Artificial Language Learning (All)mentioning
confidence: 83%
“…There is, indeed, evidence that some songbirds are sensitive to variation in pitch, amplitude and song syllable duration in their natural song [11]. Also, some mammal and bird species show a sensitivity to the general prosodic patterns in human speech [12][13][14][15][16]. These findings suggest a similar sensitivity for prosodic cues in humans and nonhuman animals.…”
Section: Introductionmentioning
confidence: 93%